Direct Instantaneous Torque Control of 4 Phase 8/6 Switched Reluctance Motor - Srinivas Pratapgiri; P.V.N. Prasad (Institute of Advanced Engineering and Science, 2011)
The applications of Switched Reluctance Motor Drives has increased in the recent past because of advantages like simple structure, no rotor winding, high torque to weight ratio, adaptability to harsh environments like coal mining etc. But the main disadvantage is that torque ripple is high because of the double saliency. This paper presents a high dynamic control technique called Direct Instantaneous Torque Control (DITC) where in the torque is maintained within a hysteresis band by changing the switching states of the phases between 1, 0 or -1.Thus torque ripple minimization is an inherent property of DITC. DITC based SRM drive is simulated in MATLAB/SIMULINK environment and results are discussed elaboratelyDOI: http://dx.doi.org/10.11591/ijpeds.v1i2.102